CLINICAL EVALUATION OF THE RAPID ACCESS VITREAL INJECTION GUIDE: A Handheld Instrument for Assisting Intravitreal Injections. Issue 4 (April 2017) - Han, Dennis P.; McKenney, Kaitlin C.; Kim, Judy E.; Weinberg, David V.; Musch, David C.; Singh, Ravi S. J.
Abstract : Purpose: The Rapid Access Vitreal Injection (RAVI) guide combines the function of an eyelid speculum and measuring caliper into a single instrument for assisting intravitreal injections. This study clinically evaluated the RAVI guide with respect to patient acceptance, complication rates, and operative goals. Methods: A prospective study was performed on 54 patients undergoing intravitreal injections using the RAVI guide (n = 32) or the speculum/caliper (n = 22). Device-related pain was assessed using the Wong-Baker scoring system, scaled from 0 (no pain) to 10 (agonizing pain). Results: Mean device-related pain score did not differ significantly between the 2 groups, with scores of 0.6 and 0.7 for the RAVI guide and speculum groups, respectively. The rate of significant pain (score of ≥2) was twice as high in the speculum group (7 of 22, 32%) compared with the RAVI guide group (5 of 32, 16%), but this difference was not statistically significant ( P = 0.19, Fisher's exact test). Operative goals of avoiding needle touch to lashes/lids and guiding needle insertion to the intended site were achieved in all patients. Conclusion: The RAVI guide appeared equivalent to the eyelid speculum in achieving operative goals, with similarly low pain scores. It has the potential for facilitating efficient, accurate, and safe intravitreal injections. Abstract : Supplemental Digital Content is Available in the Text.The Rapid Access Vitreal Injection guide combines the function of an eyelid speculum and measuring caliper into a single instrument for assisting intravitreal injections. It has the potential for facilitating efficient, accurate, and safe intravitreal injections.